THE LEVEL OF MATERNAL KNOWLEDGE ON CHILDHOOD STIMULATION AND ITS ASSOCIATION WITH CHILD DEVELOPMENT IN - Nurul Amalia Amir; Juliastuti; Putri Santy (Journal of Midwifery and Community Health (JMCH), 2022)
Introduction: The future of a nation depends on the success of children in achieving optimal growth and development. The first years of life, especially the period from the fetus in the womb until the child is 2 years old, is a very important period in child development. Approximately 16% of toddlers in Indonesia experience developmental disorders which include brain development disorders, hearing disorders, and motor disorders. Methods: This study was conducted using an analytical descriptive method with a cross sectional. The sample used in this study was 81 mothers and toddlers in the working area of Puskesmas Banda Raya. Bivariate analysis using Kendall Tau with 95% confidence interval. Result: Kendall-Tau test showed that there was an association between maternal knowledge of childhood stimulation with child development. Conclusion: Mothers with good knowledge of stimulating child growth and development are likely to have children with age-appropriate development.